The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/art.21398
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the novel proinflammatory cytokine high mobility group box chromosomal protein 1 in skin lesions of patients with lupus erythematosus

Abstract: Objective. To investigate the role of the novel cytokine high mobility group box chromosomal protein 1 (HMGB-1) in the pathogenesis of cutaneous lupus erythematosus (CLE).Methods. Punch biopsy specimens of lesional and unaffected skin from 10 patients with CLE and 3 healthy control subjects were investigated. Immunohistochemical staining for HMGB-1, tumor necrosis factor ␣ (TNF␣), and interleukin-1␤ (IL-1␤) was performed on consecutive sections. Analysis of single-nucleotide polymorphisms of ؊308 TNF was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 22 publications
4
106
1
1
Order By: Relevance
“…Human atherosclerotic plaques, but not normal arteries, have been shown to produce extracellular HMGB-1 (29,30). Furthermore, in recent studies of autoimmune inflammatory conditions, increased expression of HMGB-1 was detected by immunohistochemical staining in skin lesions of patients with lupus erythematosus, and in the salivary glands of patients with Sjogren's syndromeindicating that HMGB-1 is involved in the inflammatory process of these diseases (31,32). Further studies, including tissue studies and HMGB-1 expression in urine may, therefore, clarify the role of HMGB-1, its significance in CKD, and whether its biological activity is also a marker of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Human atherosclerotic plaques, but not normal arteries, have been shown to produce extracellular HMGB-1 (29,30). Furthermore, in recent studies of autoimmune inflammatory conditions, increased expression of HMGB-1 was detected by immunohistochemical staining in skin lesions of patients with lupus erythematosus, and in the salivary glands of patients with Sjogren's syndromeindicating that HMGB-1 is involved in the inflammatory process of these diseases (31,32). Further studies, including tissue studies and HMGB-1 expression in urine may, therefore, clarify the role of HMGB-1, its significance in CKD, and whether its biological activity is also a marker of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was recently shown that HMGB1 and RAGE mediate TLR9-dependent activation of plasmacytoid dendritic cells by DNA-containing immune complexes (41). Anti-HMGB1 Abs are found in SLE patients (42), whereas increased extracellular expression of HMGB1 is present in lupus skin lesions (43). Importantly, nephritogenic anti-dsDNA inducing Th cell lines derived from patients with active lupus nephritis proliferate in response to HMGB.…”
Section: Discussionmentioning
confidence: 99%
“…Melinda Magna 1 and David S Pisetsky of characteristic tissue pathology (for example, arthritis) or functional disturbance (for example, muscle weakness in myositis) by HMGB1 in in vitro or in vivo models; and (d) effectiveness of agents directed at HMGB1 in animal models (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Table 1 lists diseases in which studies implicate a role of HMGB1 in pathogenesis.…”
Section: The Role Of Hmgb1 In the Pathogenesis Of Inflammatory And Aumentioning
confidence: 99%